2013
DOI: 10.1111/jgh.12088
|View full text |Cite
|
Sign up to set email alerts
|

Large primary hepatocellular carcinoma: Transarterial chemoembolization monotherapy versus combined transarterial chemoembolization‐percutaneous microwave coagulation therapy

Abstract: TACE combined with PMCT had advantages in prolonging OS with satisfying time to progression and improving liver function in patients with large unresectable HCC. The results suggest that further prospective studies are required to confirm the findings of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Previously, two retrospective studies demonstrated the superior treatment effectiveness of the TACE-MWA combination therapy compared with the TACE monotherapy for specific HCC patients (7,8). However, their studies did not specify the BCLC stage and included HCC patients at BCLC stages A, B, and C. Our study focused mainly on BCLC stage B patients with tumor size ≤7 cm and tumor number ≤5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, two retrospective studies demonstrated the superior treatment effectiveness of the TACE-MWA combination therapy compared with the TACE monotherapy for specific HCC patients (7,8). However, their studies did not specify the BCLC stage and included HCC patients at BCLC stages A, B, and C. Our study focused mainly on BCLC stage B patients with tumor size ≤7 cm and tumor number ≤5.…”
Section: Discussionmentioning
confidence: 99%
“…therapy of TACE and MWA led to better outcome than TACE monotherapy for specific HCC patients (7,8), but their studies did not specify the BCLC stage of included patients. Currently, no clinical guideline clearly defines the indication of combination therapy in BCLC stage B patients.…”
mentioning
confidence: 99%
“…Given that MWA can create a larger ablation zone, MWA alone or combined with TACE has increasingly been used in treating large HCC [76,77,78]. Abdelaziz et al [78] recently performed a study to compare the efficacy and safety of percutaneous MWA with TACE for large tumors (5-7 cm) and demonstrated better results for MWA than TACE in managing large HCC lesions.…”
Section: Local Ablative Therapymentioning
confidence: 99%
“…Abdelaziz et al [78] recently performed a study to compare the efficacy and safety of percutaneous MWA with TACE for large tumors (5-7 cm) and demonstrated better results for MWA than TACE in managing large HCC lesions. Another retrospective study [77] compared the outcomes of TACE combined with MWA (TACE-MWA) with TACE for treating unresectable large HCC (≥5.0 cm in diameter). The results showed that TACE-MWA had advantages in prolonging OS, with satisfying times to progression and improving liver function.…”
Section: Local Ablative Therapymentioning
confidence: 99%
“…Compared with single treatment regimen, the combination therapy yielded improved results regarding complete necrosis rate, tumor growth reduction and overall survival (9,10). However, the effect of microwave ablation after TACE on the hypoxic cells and subsequent vascular endothelial growth factor (VEGF) production is unclear.…”
Section: Resultsmentioning
confidence: 99%